The book of frogs : a life-size guide to six hundred species from around the world - Halliday, Tim, 1945- (Chicago : The University of Chicago Press, 2016)
With over 7,000 known species, frogs display a stunning array of forms and behaviors. A single gram of the toxin produced by the skin of the golden poison dart frog can kill 100,000 people. Male Darwin frogs carry their tadpoles in their vocal sacs for sixty days before coughing them out into the world. The wood frogs of North America freeze every winter, reanimating in the spring from the glucose and urea that prevent cell collapse. --
-- What is a frog? -- Complex life cycle -- An acoustic world -- Frogs, toads and people -- Population declines -- Amphibian diseases -- Distribution and classification -- Why the number of frog species is increasing -- The frogs.
Includes bibliographical references (pages 646-647) and indexes.
Keywords: Frogs -- Anatomy; Frogs -- Behavior